2015
DOI: 10.1111/geb.12406
|View full text |Cite
|
Sign up to set email alerts
|

Modes of functional biodiversity control on tree productivity across the European continent

Abstract: Aim The relative contribution of community functional diversity and composition to ecosystem functioning is a critical question in ecology in order to enable better predictions of how ecosystems may respond to a changing climate.However, there is little consensus about which modes of functional biodiversity are most important for tree growth at large spatial scales. Here we assessed the relative importance of climate, functional diversity and functional identity (i.e. the communitymeanvalues of four key functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
94
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(116 citation statements)
references
References 101 publications
(79 reference statements)
12
94
1
5
Order By: Relevance
“…Our results confirmed our hypothesis of a general positive effect of tree species mixing on species growth across the three research approaches, although this effect was nonsignificant in the experiments. Our findings are also in line with studies that investigated the same inventory dataset and found positive effect of tree diversity on the productivity of the whole tree community(Ruiz-Benito et al, 2014;Ratcliffe et al, 2016;Ruiz-Benito et al, 2017), although we investigated the effects on individual species and manipulated the inventory dataset to make it compatible to the exploratories. In the exploratory and inventory dataset, tree species showed, on average, an increase of 27% and 20% in growth in mixed as compared to monospecific stands.…”
supporting
confidence: 88%
“…Our results confirmed our hypothesis of a general positive effect of tree species mixing on species growth across the three research approaches, although this effect was nonsignificant in the experiments. Our findings are also in line with studies that investigated the same inventory dataset and found positive effect of tree diversity on the productivity of the whole tree community(Ruiz-Benito et al, 2014;Ratcliffe et al, 2016;Ruiz-Benito et al, 2017), although we investigated the effects on individual species and manipulated the inventory dataset to make it compatible to the exploratories. In the exploratory and inventory dataset, tree species showed, on average, an increase of 27% and 20% in growth in mixed as compared to monospecific stands.…”
supporting
confidence: 88%
“…Reported relationships were positive (Schmid, 2002;Meinen et al, 2009a;Brassard et al, 2011, Brassard et al, 2013Laclau et al, 2013;Bu et al, 2017;Ma and Chen, 2017;Sun et al, 2017), insignificant (Hendricks and Bianchi, 1995;Schmid and Kazda, 2002;Bauhus et al, 2000;Meinen et al, 2009b, Meinen et al, 2009cJacob et al, 2010, Jacob et al, 2013Brassard et al, 2013;Lei et al, 2012b;Domisch et al, 2015;Ma and Chen, 2017) or negative (Bolte and Villanueva, 2006). The more numerous studies between tree species diversity and above-ground biomass and biomass production of trees show more consistent positive diversity effects (Zhang et al, 2012;Gamfeldt et al, 2013;Vilà et al, 2013;Ratcliffe et al, 2015;Toïgo et al, 2015;Wu et al, 2015;Jucker et al, 2016;Liang et al, 2016;Pretsch and Schütze, 2016), suggesting that tree species diversity effects on above-ground biomass or productivity are not necessarily mirrored by tree fine root productivity (Bauhus et al, 2000;Chen and Klinka, 2003;Brassard et al, 2011;Lei et al, 2012a). There are no comprehensive studies explaining the inconsistent responses of fine root biomass or productivity to tree species diversity.…”
Section: Introductionmentioning
confidence: 99%
“…There are no comprehensive studies explaining the inconsistent responses of fine root biomass or productivity to tree species diversity. The varying above-ground biomass and productivity responses have been related to different climatic conditions and site productivity (Paquette and Messier, 2011;Jucker et al, 2014a, Jucker et al, 2016Potter and Woodall, 2014;Ratcliffe et al, 2015;Toïgo et al, 2015;Wu et al, 2015), suggesting that responses are positive under cold or dry climatic conditions and at low site productivity. Thus, systematic studies covering a wide range of mature forest ecosystems and tree species and their combinations are still needed to understand below-ground productivity responses to tree species diversity, identity, stand characteristics and soil properties.…”
Section: Introductionmentioning
confidence: 99%
“…Data reuse allows to extend the scope of studies in order to cover wider temporal and spatial scales which are relevant to human societies and which help to generalize theory across environmental contexts. For example, meta-analyses reusing data from scattered experiments have allowed to develop the theory of multifunctionality in biodiversity/ecosystem functioning research [5], and extended functional biodiversity research from plots to continents [6] and the parameterization of global climate models [7]. Although the reuse of data is important for research in ecology it can be challenging to find suitable data which qualifies for the reuse in a specific context and which comes with context data necessary for an integration into meta-analyses.…”
Section: Introductionmentioning
confidence: 99%